Nursing of a newborn with congenital bilateral chylothorax (1例先天性双侧乳糜胸早产儿的护理体会) - JIANG Ziying (蒋子英); HUANG Haiying (黄海缨); CHEN Biao (陈彪); ZHANG Yichun (张一春) (中西医结合护理)
This paper summarized the nursing practicve of a newborn with congenital bilateral chylothorax. The key points of nursing included intensive nursing management of airway, closed thoracic drainage nursing, correct evaluation of neonatal pain and corresponding nursing measures, nursing and observation of special medication, strict implementation of disinfection and isolation measures, and total parenteral and enteral nutrition nursing at the same time. After careful treatment and nursing, the newborn baby was cured and discharged on the 44th day of hospitalization. (本文总结1例先天性双侧乳糜胸早产儿的护理经验。护理重点包括气道集束化护理管理; 胸腔闭式引流护理; 新生儿疼痛评估及管理; 特殊用药的护理及观察; 严格落实消毒隔离措施; 同时做好全胃肠外及肠内营养护理; 实施早产儿发育支持护理。经过精心的治疗与护理, 患儿于住院第44天治愈出院。)